MEASURING THE EFFICIENCY OF WORLD VISION GHANA’S EDUCATIONAL PROJECTS USING DATA ENVELOPMENT ANALYSIS - Charles, Sebil; Napoleon Bellua, Sam; Jude, Bumbokuri (European Scientific Journal, ESJ, 2013)
In the current era, donors are more interested in value for their money and are now keener about how their hard earned money is being used. As such Non-governmental organisations face crucial decisions as resources become scarcer. Based on these, more efficient use of resources becomes more important than ever before. This work therefore evaluates the performance of Educational Projects of four Area Development Programmes of World Vision Ghana using Data Envelopment Analysis Approach. The Data for the four Area Development Programmes (ADP) and their respective District Education Offices for the year 2010 were obtained. The two inputs that were recognised were number of staff and number of vehicles. We also identified two outputs as BECE pass rate and completion rate at JHS level. The results revealed that two Area Development Programmes (Zabzugu ADP and Gushegu ADP) were identified as efficient. Two Area Development Programmes (Saboba ADP and Nadowli ADP) were marked out as inefficient. To improve the performance of any inefficient Area Development Programme, one of the efficient ADP was set as a benchmark